First tsunami gravity wave detection in ionospheric radio occultation data. Issue 5 (9th May 2015) - Coïsson, Pierdavide; Lognonné, Philippe; Walwer, Damian; Rolland, Lucie M.
<x xml:space="preserve">Abstract</x> After the 11 March 2011 earthquake and tsunami off the coast of Tohoku, the ionospheric signature of the displacements induced in the overlying atmosphere has been observed by ground stations in various regions of the Pacific Ocean. We analyze here the data of radio occultation satellites, detecting the tsunami‐driven gravity wave for the first time using a fully space‐based ionospheric observation system. One satellite of the Constellation Observing System for Meteorology, Ionosphere and Climate (COSMIC) recorded an occultation in the region above the tsunami 2.5 h after the earthquake. The ionosphere was sounded from top to bottom, thus providing the vertical structure of the gravity wave excited by the tsunami propagation, observed as oscillations of the ionospheric Total Electron Content (TEC). The observed vertical wavelength was about 50 km, with maximum amplitude exceeding 1 total electron content unit when the occultation reached 200 km height. We compared the observations with synthetic data obtained by summation of the tsunami‐coupled gravity normal modes of the Earth/Ocean/atmosphere system, which models the associated motion of the ionosphere plasma. These results provide experimental constraints on the attenuation of the gravity wave with altitude due to atmosphere viscosity, improving the understanding of the propagation of tsunami‐driven gravity waves in the upper atmosphere. They demonstrate that the amplitude of the tsunami can be estimated to within 20% by the recorded ionospheric data.